Experimental Study on Wave Nonlinear Characteristics at a Complex Uneven Fringing Reef - Wang Chao; Qu Ke; Wang Xu; Chen Jiaying; Wang Aoyu (Redai dili, 2025)
In this study, the variation law of nonlinear characteristic parameters of waves near islands and reefs with different slopes was examined through physical model tests. The main conclusions are as follows: (1) When a regular wave propagates to the shallow water area of the first reef flat, the peak becomes steep, the trough becomes flat, and the wave surface presents a shape similar to an elliptical cosine wave. The wave shallowing deformation near the reef flat steps reaches the limit, the amplitude increases significantly, and the front surface of the wave peak becomes steep and gradually asymmetric. The wave breaks on the second reef flat, the wave energy transfers from the main wave frequency to the high frequency, the traveling wave is regenerated, and an obvious secondary wave peak appears. (2) In the process of wave propagation from the far-sea end to the vicinity of the reef edge, because of the shallowing deformation, high-order constrained harmonics are generated, which makes the wave surface asymmetric along the horizontal axis and vertical axis. The amplitude of the wave skewness, asymmetry, and peak of the Usser number reaches a maximum near the reef flat step and then decreases rapidly on the second reef flat. The wave surface gradually approaches symmetry in the direction of the horizontal axis and the vertical axis. The amplitudes of the three nonlinear characteristic parameters increases with the increase in incident wave height and wave period and decreases with the increase in reef flat water depth. (3) When the nonlinearity of the incident wave is stronger, the asymmetry and skewness are larger. As the Eser number increased, the wave skewness showed a positive correlation with the increasing trend, while the asymmetry showed a negative correlation with the decreasing trend. A certain correlation was observed between the wave skewness and asymmetry on the reef flat with different slope and the local Ursell number. Based on this result, this study proposes a set of empirical formulas for wave skewness and asymmetry parameters on reef flat with different slope angle.This study enriches the hydrodynamic theory of complex coral reef coasts and lays a foundation for further research on the ecological environment protection and coastal evolution mechanism in the sea area near coral reefs. However, this study only discusses the variation law of wave nonlinear characteristic parameters near islands and reefs with different slopes under the influence of wave factor changes. In the future, the influence of differences of island topography on wave nonlinearity should be studied in greater detail.